2011
DOI: 10.1186/1471-2458-11-476
|View full text |Cite
|
Sign up to set email alerts
|

Assessing young unmarried men's access to reproductive health information and services in rural India

Abstract: BackgroundWe investigated the accessibility of reproductive health information and contraceptives in a relatively less developed area of rural central India and assessed the risks facing young unmarried men.MethodsThis cross-sectional study used both qualitative and quantitative methods. Participants included 38 unmarried rural men in four focus-group discussions and a representative sample of 316 similarly profiled men, aged 17-22 years, in a survey. Information was collected on the men's socioeconomic charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 17 publications
1
33
0
2
Order By: Relevance
“…We found that females received SRH information mainly from health personnel but most males responded that they received SRH information from unreliable sources, such as friends or older youths in their community. This finding was also evident in a study among Indian male youths in which participants happened to receive SRH information from unreliable sources [26]. …”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…We found that females received SRH information mainly from health personnel but most males responded that they received SRH information from unreliable sources, such as friends or older youths in their community. This finding was also evident in a study among Indian male youths in which participants happened to receive SRH information from unreliable sources [26]. …”
Section: Discussionmentioning
confidence: 52%
“…A study conducted among young-unmarried men in India showed that these men also received SRH information mainly from the mass media [26]. In contrast, mass media was significantly associated with beliefs that increased the likelihood of sexual exposure among adolescents in the US [30], a finding which highlights the importance of mass media among male youths and its ambiguous effects on their RH behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…Youth’s concerns with confidentiality were both about the potential of being seen or overheard and about the provider’s ability to ensure confidentiality [19, 21, 22, 25, 26, 2933]. Youth frequently feared being seen by friends and other members of the community, particularly by those who could tell their parents.…”
Section: Resultsmentioning
confidence: 99%
“…It would mean that we were doing something wrong. [… ]If someone saw me buying a condom, word would spread” (Unmarried Male, India) [26]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation